THE EFFECTS OF BUD SIZES AND BENZYLADENINE ON IN VITRO PROPAGATION OF CURCUMA AERUGINOSA ROXB.H. - Dheeranupattana, Srisulak; Palee, Jiraporn; Jatisatienr, Araya (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Curcuma aeruginosa Roxb.H is one of the most valuable oriental herbs. Its rhizome extract has been used as antifungal agent and reported to have anticarcinogenic activity in animals. Natural propagation by rhizome is very poor and can not be done in winter because of its dormancy. The objective of this study was to investigate the effects of bud sizes and benzyladenine (BA) on in vitro propagation of C. aeruginosa. Buds in various sizes were cultured on Murashige and Skoog (MS) media under 1,500 lux of light intensity at 25OC for 4 weeks. It was found that 3.0 – 4.0 cm buds provided 66.67% survival, produced 100% shoots and gave the highest numbers of 2 shoots per explant. To determine the effect of BA, 3.0 – 4.0 cm buds, was also cultured on MS media supplemented with 0, 1, 2 and 3 mg/l of BA under the same condition for 4 weeks. The MS medium with 1 mg/l BA was found to induce 100% shoot formation with an average of 2.27 shoots per explant and induced the highest root formation of 72.73 %. Acknowledgements: This research was supported by Faculty of Science, Chiang Mai University, Thailand.